2018
DOI: 10.1039/c7sc03306k
|View full text |Cite
|
Sign up to set email alerts
|

3D chemical imaging of the brain using quantitative IR spectro-microscopy

Abstract: Here, we introduce a unique high-throughput infrared (IR) microscopy method that combines automated image correction and subsequent spectral data analysis for 3D-IR image reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…SR-IR is 100-1000 times brighter than the traditional light source, enabling fourier transform infrared spectromicrotomography (FTIR-μCT) to reconstruct the image in the micron scale. By SR X-ray correction [42,43], IR was used to construct a 3D mapping of in-situ content of glucose, glycogen, and lactate in the brain of mice [44]. Transition metal homeostasis, such as copper, iron, and zinc, is an important property of brain and plays an important role in stroke and other brain diseases [45][46][47].…”
Section: Synchrotron Radiationmentioning
confidence: 99%
“…SR-IR is 100-1000 times brighter than the traditional light source, enabling fourier transform infrared spectromicrotomography (FTIR-μCT) to reconstruct the image in the micron scale. By SR X-ray correction [42,43], IR was used to construct a 3D mapping of in-situ content of glucose, glycogen, and lactate in the brain of mice [44]. Transition metal homeostasis, such as copper, iron, and zinc, is an important property of brain and plays an important role in stroke and other brain diseases [45][46][47].…”
Section: Synchrotron Radiationmentioning
confidence: 99%
“…Ogunleke et al demonstrated a high-throughput infrared microscopy method that utilized automated image correction followed by spectral analysis for 3D FTIR image reconstruction. The new approach enabled quantitative metabolic parameter extraction from the FTIR spectra for the characterization of the brain tumor metabolism [ 130 ]. Metasurface-enhanced infrared reflection spectroscopic cytopathology has been developed that utilizes plasmonic metasurfaces to localize and intensify the evanescent field near the cell’s membrane, and to conduct spectroscopic interrogations of the cells attached to the metasurface using reflected infrared light.…”
Section: Clinical Translation Of Ftirmentioning
confidence: 99%
“…10 To achieve 3D chemical imaging of a complete organ, a high throughput infrared microscopy method was established by combining Xray tomography and subsequent data analysis. 11 Moreover, optoacoustic imaging has been proven to be a new sensing method capable of deep penetration with a higher spatial resolution compared to uorescence imaging. In addition, a library screening approach was utilized to identify and evaluate the available dyes for multi-spectral optoacoustic tomography (MSOT) imaging.…”
mentioning
confidence: 99%